Solid polymer electrolyte membrane, membrane electrode assembly, method for producing membrane electrode assembly, and water electrolysis device
By using an electrolyte membrane containing fluoropolymer containing ion exchange groups, platinum, cerium oxide and woven fabrics in the water electrolytic device, the problems of hydrogen penetration and material decomposition are solved, and efficient hydrogen recovery and long-life electrolyte membrane are achieved.
Patent Information
- Application Number
- CN202380065466.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-09-12
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing solid polymer type water electrolytic device, the penetration of hydrogen gas leads to a decrease in recovery efficiency, and fluoropolymers are prone to decomposition during operation, resulting in insufficient chemical durability.
A solid polymer electrolyte membrane containing fluoropolymers with ion exchange groups, platinum, cerium oxides and woven fabrics is used to improve the low gas permeability and chemical durability of the membrane by optimizing the material composition and structural design.
It realizes a solid polymer electrolyte membrane with excellent low gas permeability and chemical durability, reduces the risk of hydrogen penetration and material decomposition, and improves the performance and reliability of the water electrolytic device.
Smart Images

Figure CN119895082A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a solid polymer electrolyte membrane, a membrane electrode assembly, a method for manufacturing the membrane electrode assembly, and a water electrolysis device. Background Art
[0002] From the perspective of power-to-gas, that is, converting surplus electricity into gas for storage and utilization, the use of solid polymer water electrolysis devices (PEM water electrolysis devices) is being studied.
[0003] For example, Patent Document 1 discloses a solid polymer water electrolysis device having a membrane electrode assembly including: an anode and a cathode each having a catalyst layer; and a solid polymer electrolyte membrane disposed between the anode and the cathode.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2022 / 050363 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] In recent years, further performance improvement of water electrolysis devices is required, specifically, reduction of hydrogen penetration (crossover) is required. Here, hydrogen penetration refers to the movement of hydrogen generated at the cathode to the anode side through the solid polymer electrolyte membrane in the water electrolysis device. If hydrogen penetration occurs, there is a problem of reduced hydrogen recovery efficiency. Therefore, it is required that the solid polymer electrolyte membrane can suppress the penetration of hydrogen generated in the system, that is, low gas permeability.
[0009] In addition, when a solid polymer electrolyte membrane is used in a water electrolysis device, the fluorinated polymer in the solid polymer electrolyte membrane may be decomposed by compounds (eg, hydrogen peroxide) generated in the system during operation. Therefore, a solid polymer electrolyte membrane with excellent chemical durability is required.
[0010] The present inventors evaluated a water electrolysis device having a solid polymer electrolyte membrane as described in Patent Document 1 and found that there is room for improvement in at least one of low gas permeability and chemical durability of the solid polymer electrolyte membrane.
[0011] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a solid polymer electrolyte membrane having low gas permeability and excellent chemical durability, a membrane electrode assembly, a method for producing the membrane electrode assembly, and a water electrolysis device.
[0012] Solutions for solving problems
[0013] The present inventors have conducted intensive studies on the above-mentioned problems and have found that the desired effects can be obtained by using a solid polymer electrolyte membrane comprising a fluorinated polymer having ion exchange groups, a platinum-containing material, a cerium oxide and a woven fabric, thereby completing the present invention.
[0014] That is, the inventors have found that the above-mentioned problems can be solved by the following configuration.
[0015] [1] A solid polymer electrolyte membrane, characterized in that it comprises: a fluorine-containing polymer having ion exchange groups, a platinum-containing material, a cerium oxide, and a woven fabric.
[0016] [2] The solid polymer electrolyte membrane according to [1], wherein the ion exchange capacity of the fluorinated polymer is 0.90 to 2.00 milliequivalents / g dry resin.
[0017] [3] The solid polymer electrolyte membrane according to [1] or [2], wherein the average 1 cm 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.010 mg / cm 2 above.
[0018] [4] The solid polymer electrolyte membrane according to any one of [1] to [3], wherein the average 1 cm 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.132 mg / cm 2 above.
[0019] [5] The solid polymer electrolyte membrane according to any one of [1] to [4], wherein the average 1 cm 2 The mass of the platinum-containing substance in the solid polymer electrolyte membrane is 0.030 mg / cm 2 above,
[0020] Average 1cm 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.132 mg / cm 2 above.
[0021] [6] The polymer electrolyte membrane according to any one of [1] to [5], wherein the platinum-containing substance is predominantly present on one surface side of the polymer electrolyte membrane.
[0022] [7] The solid polymer electrolyte membrane according to any one of [1] to [6], wherein the platinum-containing substance is supported on a carrier.
[0023] [8] The polymer electrolyte membrane according to any one of [1] to [7], wherein the ion exchange group of the fluorinated polymer is a sulfonic acid type functional group.
[0024] [9] The solid polymer electrolyte membrane according to any one of [1] to [8], wherein the fluorinated polymer comprises at least one unit selected from the group consisting of a unit represented by formula (1-3) and a unit represented by formula (1-4).
[0025] In the formula (1-3) and formula (1-4) described below, R f1 is a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f2 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f3 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, r is 0 or 1, m is 0 or 1, and M is each independently a hydrogen atom, an alkali metal or a quaternary ammonium cation.
[0026]
[10] The polymer electrolyte membrane according to any one of [1] to [9], wherein the woven fabric is made of a material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyetheretherketone and polyphenylene sulfide.
[0027]
[11] A membrane electrode assembly, comprising:
[0028] The solid polymer electrolyte membrane according to any one of [1] to
[10] ,
[0029] a cathode catalyst layer disposed on one side of the solid polymer electrolyte membrane, and
[0030] An anode catalyst layer is disposed on the other surface of the solid polymer electrolyte membrane.
[0031]
[12] A water electrolysis device, characterized by comprising:
[0032]
[11] The membrane electrode assembly described in claim 1;
[0033] a power supply unit connected to the cathode catalyst layer side and the anode catalyst layer side of the membrane electrode assembly; and
[0034] A water supply unit supplies water to the anode catalyst layer side.
[0035]
[13] A method for manufacturing a membrane electrode assembly, wherein the membrane electrode assembly comprises the solid polymer electrolyte membrane described in any one of [1] to
[10] , a cathode catalyst layer and an anode catalyst layer, wherein in the manufacturing method, the cathode catalyst layer is formed on one side of the solid polymer electrolyte membrane, and the anode catalyst layer is formed on the other side of the solid polymer electrolyte membrane.
[0036] Effects of the Invention
[0037] According to the present invention, a solid polymer electrolyte membrane having low gas permeability and excellent chemical durability, a membrane electrode assembly, a method for producing the membrane electrode assembly, and a water electrolysis device can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a schematic cross-sectional view of an electrolyte membrane for explaining a state in which a platinum-containing substance is present in a predominantly high concentration.
[0039] Figure 2 This is a cross-sectional view schematically showing an example of the membrane electrode assembly of the present invention.
[0040] Figure 3 This is a cross-sectional view schematically showing another example of the membrane electrode assembly of the present invention. DETAILED DESCRIPTION
[0041] The definitions of the following terms apply throughout the entire specification and claims unless otherwise specified.
[0042] The "ion exchange group" refers to a group that can exchange at least a part of the ions contained in the group for other ions, and examples thereof include the following sulfonic acid type functional group and carboxylic acid type functional group.
[0043] The "sulfonic acid type functional group" refers to a sulfonic acid group (-SO3H) or a sulfonate group. Here, as a form of a sulfonate group, for example, (-SO3 - )Ma + 、(-SO3 - )2Mb 2+ 、and、(-SO3 - )3Mc 3+ (Among them, Ma + is an alkali metal ion or a quaternary ammonium cation, Mb 2+ is a divalent metal ion, Mc 3+ It should be noted that when there are two ligands, the number of ion exchange groups is counted as 2, and when there are three ligands, the number of ion exchange groups is counted as 3.
[0044] The "carboxylic acid type functional group" refers to a carboxylic acid group (-COOH) or a carboxylate group. Here, as a form of a carboxylate group, for example, (-CO - )Ma + 、(-COO - )2Mb 2+ , and, (-COO - )3Mc 3+ Can be cited (among which, Ma + is an alkali metal ion or a quaternary ammonium cation, Mb 2+is a divalent metal ion, Mc 3+ It should be noted that when there are two ligands, the number of ion exchange groups is counted as 2, and when there are three ligands, the number of ion exchange groups is counted as 3.
[0045] "Precursor membrane" refers to a membrane comprising a polymer having groups that can be converted into ion exchange groups.
[0046] The "group convertible into an ion exchange group" refers to a group convertible into an ion exchange group by a treatment such as a hydrolysis treatment or an acidification treatment.
[0047] The "group convertible into a sulfonic acid type functional group" refers to a group convertible into a sulfonic acid type functional group by a treatment such as a hydrolysis treatment or an acidification treatment.
[0048] The "group convertible into a carboxylic acid type functional group" refers to a group convertible into a carboxylic acid type functional group by a known treatment such as a hydrolysis treatment or an acidification treatment.
[0049] The "unit" in a polymer refers to an atomic group derived from one molecule of a monomer formed by polymerization of the monomer. The unit may be an atomic group directly formed by a polymerization reaction, or an atomic group in which a part of the atomic group is converted into another structure by treating a polymer obtained by a polymerization reaction.
[0050] The numerical range represented by "to" refers to a range including the numerical values recorded before and after "to" as the lower limit and the upper limit. In the numerical range recorded in stages in this specification, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in this specification, the upper limit or lower limit recorded in a certain numerical range can also be replaced by the value shown in the embodiment.
[0051] [Electrolyte membrane]
[0052] The solid polymer electrolyte membrane of the present invention (hereinafter, also simply referred to as "electrolyte membrane") is the following solid polymer electrolyte membrane, which comprises: a fluorine-containing polymer having ion exchange groups (hereinafter, also simply referred to as "fluorine-containing polymer (I)"), a platinum-containing material, cerium oxide and woven fabric.
[0053] When the electrolyte membrane of the present invention is applied to a water electrolysis device, it is presumed that the hydrogen generated on the cathode side reacts with the oxygen generated on the anode side on the platinum-containing material contained in the electrolyte membrane to form water, thereby suppressing the movement of hydrogen to the anode side (hydrogen penetration). For such reasons, it is believed that the electrolyte membrane of the present invention has excellent low gas permeability.
[0054] In addition, when the electrolyte membrane of the present invention is applied to a water electrolysis device, it is presumed that the OH radicals generated by hydrogen peroxide generated in the system during operation are quenched by cerium ions dissociated from the cerium oxide contained in the electrolyte membrane, and as a result, the decomposition of the fluorinated polymer (I) can be suppressed. For this reason, it is believed that the chemical durability of the electrolyte membrane of the present invention is also excellent.
[0055] In addition, when the electrolyte membrane of the present invention is applied to a water electrolysis device, the hydrogen generated on the cathode side reacts with the oxygen generated on the anode side on the platinum-containing material contained in the electrolyte membrane to form water, thereby reducing the amount of hydrogen peroxide generated, and the platinum-containing material itself can decompose hydrogen peroxide, thereby reducing the amount of OH radicals generated. For this reason, the electrolyte membrane of the present invention is also considered to have excellent chemical durability.
[0056] The electrolyte membrane may be a single-layer structure or a multi-layer structure. Specific forms of the electrolyte membrane as a multi-layer structure include a form in which a plurality of electrolyte layers containing at least one of platinum and cerium oxide are stacked and the content thereof is different from each other, and a form in which a plurality of electrolyte layers having different ion exchange capacities are stacked and the like.
[0057] The platinum-containing substance and cerium oxide contained in the electrolyte membrane may be dispersed in the whole electrolyte membrane, or may be concentrated on one surface side of the electrolyte membrane. It is preferred that at least one of the platinum-containing substance and the cerium oxide is concentrated on one surface side of the electrolyte membrane, and it is preferred that at least the platinum-containing substance of the platinum-containing substance and the cerium oxide is concentrated on one surface side of the electrolyte membrane. In addition, the platinum-containing substance and the cerium oxide (i.e., both the platinum-containing substance and the cerium oxide) may be concentrated on one surface side of the electrolyte membrane.
[0058] In addition, when the electrolyte membrane is applied to a water electrolysis device, it is preferred to arrange the surface of the electrolyte membrane on the side where the platinum-containing substance is more heavily present on the anode side in order to further suppress the occurrence of hydrogen crossover. In this case, the catalyst contained in the catalyst layer of the anode preferably contains iridium oxide in order to achieve the above-mentioned better effect.
[0059] In the present specification, "platinum-containing substances are concentrated on one surface side of the electrolyte membrane" means that the concentration of platinum-containing substances in the region from one surface of the electrolyte membrane (hereinafter also referred to as "surface A") to a specified depth position (hereinafter also referred to as "depth position B") before reaching the other surface (hereinafter also referred to as "surface C") is higher than the concentration of platinum-containing substances in the region from surface C to depth position B.
[0060] Furthermore, “cerium oxide is concentrated on one surface side of the electrolyte membrane” means that the concentration of cerium oxide in the region from surface A to depth position B is higher than that in the region from surface C to depth position B.
[0061] In addition, “platinum-containing substances and cerium oxides are concentrated on one surface side of the electrolyte membrane” means that the concentration of platinum-containing substances in the region from surface A to depth position B is higher than the concentration of platinum-containing substances in the region from surface C to depth position B, and the concentration of cerium oxide in the region from surface A to depth position B is higher than the concentration of cerium oxide in the region from surface C to depth position B.
[0062] Here, as one of the preferred modes for the platinum-containing material to be distributed predominantly on one surface side of the electrolyte membrane, the following mode can be cited: a depth position B from the surface A to 50% of the membrane thickness of the electrolyte membrane 50 The concentration of the platinum-containing material in the region from the surface C to the depth position B is 50 The concentration of the platinum-containing substance in the region up to 30° is high.
[0063] use Figure 1 The example of "the platinum-containing substance is present more heavily on one surface side of the electrolyte membrane" will be specifically described. Figure 1 This is a schematic cross-sectional view of an electrolyte membrane for explaining a state in which a platinum-containing substance is present in a predominantly high concentration.
[0064] exist Figure 1 In FIG. 1 , the electrolyte membrane 1 has a surface A1 as one surface and a surface C1 as the other surface. The depth position B1 indicates the distance T from the surface A1 to the surface C1. X The length of the position.
[0065] The shortest distance T1 from the surface A1 to the surface C1 of the electrolyte membrane 1 corresponds to the thickness of the electrolyte membrane 1. X is X% of the distance T1. X When the length is 20% of the distance T1 , the depth position B1 corresponds to a position corresponding to 20% of the thickness (distance T1 ) of the electrolyte membrane 1 from the surface A1 of the electrolyte membrane 1 .
[0066] The region X indicates a region from the surface A1 to the depth position B1 , and the region Y indicates a region from the surface C1 to the depth position B1 .
[0067] In addition, when the surface of the electrolyte membrane 1 has irregularities, the above-mentioned distances are measured with reference to the position where the thickness of the electrolyte membrane 1 is the smallest.
[0068] exist Figure 1When the concentration of the platinum-containing substance in region X is higher than that in region Y, it can also be said that “the platinum-containing substance is concentrated on one surface side of the electrolyte membrane”.
[0069] For the platinum-containing substance contained in the electrolyte membrane, from the aspect of more excellent effects of the present invention, it is preferred that the platinum-containing substance exists from one surface of the electrolyte membrane to a position corresponding to 25% of the thickness of the electrolyte membrane, more preferably exists from one surface of the electrolyte membrane to a position corresponding to 20% of the thickness of the electrolyte membrane, further preferably exists from one surface of the electrolyte membrane to a position corresponding to 15% of the thickness of the electrolyte membrane, and particularly preferably exists from one surface of the electrolyte membrane to a position corresponding to 10% of the thickness of the electrolyte membrane. It is further preferred that the platinum-containing substance contained in the electrolyte membrane exists only to these film thicknesses.
[0070] The positions where the platinum-containing substance and the cerium oxide exist in the electrolyte membrane can be determined by element distribution using, for example, an energy dispersive X-ray analyzer (product name: "QUANTAX FlatQUAD", manufactured by Bruker Corporation).
[0071] Based on the obtained element distribution, the above-mentioned distance Tx can be calculated.
[0072] As an example of a method for making the platinum-containing substance be concentrated on one surface side of an electrolyte membrane, there is a method of stacking a first electrolyte layer and a second electrolyte layer to obtain an electrolyte membrane, wherein the first electrolyte layer contains the platinum-containing substance, and the concentration of the platinum-containing substance in the second electrolyte layer is lower than that in the first electrolyte layer, or the second electrolyte layer does not contain the platinum-containing substance.
[0073] Another method includes a method of impregnating a solution containing platinum ions from one surface of an electrolyte membrane not containing a platinum-containing substance so that the platinum-containing substance is contained from the one surface of the electrolyte membrane to a predetermined depth position of the electrolyte membrane.
[0074] The electrolyte membrane preferably contains substantially no thickener in view of high membrane resistance. The electrolyte membrane contains substantially no thickener means that the content of the thickener is 0.1 mass % or less, preferably 0.01 mass % or less, and more preferably 0 mass % relative to the total mass of the electrolyte membrane.
[0075] Specific examples of the thickener will be described later.
[0076] The thickness of the electrolyte membrane is preferably 30 μm or more, and preferably 400 μm or less, more preferably 300 μm or less, further preferably 200 μm or less, particularly preferably 90 μm or less, and most preferably 60 μm or less. It should be noted that when the electrolyte membrane has a multilayer structure, the thickness of the electrolyte membrane refers to the total thickness of each layer.
[0077] When the electrolyte membrane has a multilayer structure and has the above-mentioned first electrolyte layer and the above-mentioned second electrolyte layer, the ratio of the thickness of the first electrolyte layer to the thickness of the second electrolyte layer (thickness of the first electrolyte layer / thickness of the second electrolyte layer) is preferably greater than 0.02, more preferably greater than 0.05, further preferably greater than 0.12, further preferably greater than 0.19, and is preferably less than 0.80, more preferably less than 0.50, further preferably less than 0.30.
[0078] The thickness of the electrolyte membrane is measured using an enlarged image (e.g., 100 times) of a cross section of the electrolyte membrane taken using an optical microscope (product name "BX-51", manufactured by Olympus Corporation). It should be noted that when there are concave and convex portions on the surface of the electrolyte membrane, the thickness of the concave portion at 10 points in the electrolyte membrane and the thickness of the convex portion at 10 points in the electrolyte membrane are measured, and the arithmetic mean of the thickness of the total 20 points is taken as the thickness of the electrolyte membrane. Among them, in the case where the convex portion includes yarn constituting the woven fabric, the thickness of the convex portion is the value obtained by subtracting the thickness of the yarn present in the convex portion.
[0079] <Weaving>
[0080] The fabric plays a role in improving the dimensional stability, strength, and handling properties of the electrolyte membrane.
[0081] The opening ratio of the woven fabric is preferably 50% or more, more preferably 55% or more, further preferably 60% or more, and particularly preferably 70% or more, from the viewpoint of further reducing the electrolysis voltage.
[0082] From the viewpoint of achieving better strength of the membrane electrode assembly, the upper limit of the opening ratio of the woven fabric is preferably 90% or less, particularly preferably 80% or less.
[0083] The open area ratio of the woven fabric is calculated by the following formula (ε) based on the average diameter R1 of the yarns constituting the woven fabric and the average interval P1 between adjacent yarns (hereinafter also referred to as “pitch P1”) among the yarns constituting the woven fabric.
[0084] Here, the average diameter R1 of the yarn refers to the arithmetic mean of the diameters of 10 different yarns selected at random based on the magnified image (e.g., 100 times) of the woven surface obtained using a microscope. In addition, the pitch P1 refers to the arithmetic mean of 10 points at intervals of 10 points selected at random based on the magnified image (e.g., 100 times) of the woven surface obtained using a microscope.
[0085] Opening ratio of fabric (%) = [P1 / (P1+R1)] 2 ×100(ε)
[0086] The denier of the yarn constituting the woven fabric is preferably 2 or more, more preferably 10 or more, and particularly preferably 15 or more, from the viewpoint of achieving better strength and dimensional stability of the membrane electrode assembly.
[0087] From the viewpoint of being able to further reduce the electrolytic voltage, the upper limit of the denier of the yarn constituting the woven fabric is preferably 60 or less, more preferably 50 or less, and particularly preferably 20 or less.
[0088] In addition, the denier is a value expressing the mass of 9000 m of yarn in grams (g / 9000 m).
[0089] From the perspective of excellent strength and dimensional stability of the membrane electrode assembly, the density of the yarn constituting the woven fabric is preferably 50 yarns / inch or more, more preferably 70 yarns / inch or more, and particularly preferably 90 yarns / inch or more. From the perspective of further reducing the electrolysis voltage, the density of the yarn is preferably 200 yarns / inch or less, more preferably 150 yarns / inch or less, and particularly preferably 100 yarns / inch or less.
[0090] The yarn constituting the woven fabric may be composed of either a monofilament composed of one filament or a multifilament composed of two or more filaments, but is preferably composed of a monofilament.
[0091] From the perspective of better durability of the yarn, the yarns constituting the woven fabric are preferably each independently composed of a material selected from the group consisting of polytetrafluoroethylene (hereinafter also referred to as "PTFE"), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (hereinafter also referred to as "PFA"), polyetheretherketone (hereinafter also referred to as "PEEK"), and polyphenylene sulfide (hereinafter also referred to as "PPS").
[0092] The yarn constituting the woven fabric is preferably composed of slit yarns from the viewpoint of better durability and strength of the yarn.
[0093] When the material constituting the woven fabric is PTFE, the weight per unit area of the woven fabric is preferably 20 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 Above, preferably 30g / m 2 More than, in addition, preferably 40g / m 2 the following.
[0094] When the material constituting the woven fabric is PFA, the weight per unit area of the woven fabric is preferably 10 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 More than, preferably 30g / m 2 Below, more preferably 20g / m 2 the following.
[0095] When the material constituting the woven fabric is PEEK, the weight per unit area of the woven fabric is preferably 5 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 More than, preferably 40g / m 2 Below, more preferably 30g / m 2 the following.
[0096] When the material constituting the woven fabric is PPS, the weight per unit area of the woven fabric is preferably 5 g / m2 from the viewpoint of excellent balance between the strength and handling properties of the electrolyte membrane. 2 More than, preferably 40g / m 2 More preferably 30 g / m 2 the following.
[0097] The content of the woven fabric is preferably 3 mass % or more, more preferably 5 mass % or more, and is preferably 50 mass % or less, more preferably 40 mass % or less, and further preferably 30 mass % or less, based on the total mass of the electrolyte membrane.
[0098] <Fluoropolymer (I)>
[0099] The ion exchange capacity of the fluoropolymer (I) is preferably 0.90 milliequivalent / g dry resin or more, more preferably greater than 1.10 milliequivalent / g dry resin, further preferably 1.15 milliequivalent / g dry resin or more, particularly preferably 1.20 milliequivalent / g dry resin or more, and most preferably 1.25 milliequivalent / g dry resin or more, from the viewpoint of being able to further reduce the electrolysis voltage when used in a water splitting device.
[0100] The ion exchange capacity of the fluoropolymer (I) is preferably 2.00 meq / g dry resin or less, more preferably 1.50 meq / g dry resin or less, further preferably 1.43 meq / g dry resin or less, from the viewpoint of the strength of the membrane electrode assembly when containing water.
[0101] The fluorinated polymer (I) may be used alone or in the form of a stack or a mixture of two or more.
[0102] The electrolyte membrane may contain polymers other than the fluoropolymer (I), and the polymer in the electrolyte membrane is preferably substantially composed of the fluoropolymer (I). Substantially composed of the fluoropolymer (I) means that the content of the fluoropolymer (I) is 95% by mass or more relative to the total mass of the polymers in the electrolyte membrane. As the upper limit of the content of the fluoropolymer (I), 100% by mass relative to the total mass of the polymers in the electrolyte membrane can be cited.
[0103] Specific examples of other polymers other than the fluorinated polymer (I) include one or more polyazole compounds selected from the group consisting of polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and containing oxygen atoms and / or sulfur atoms.
[0104] Specific examples of the polyazole compound include polyimidazole compounds, polybenzimidazole compounds, polybenzbisimidazole compounds, polybenzoxazole compounds, polyoxazole compounds, polythiazole compounds, and polybenzothiazole compounds.
[0105] In addition, from the viewpoint of oxidation resistance of the electrolyte membrane, other polymers include polyphenylene sulfide resin and polyphenylene ether resin.
[0106] The fluorinated polymer (I) has an ion exchange group. Specific examples of the ion exchange group include sulfonic acid functional groups and carboxylic acid functional groups. Sulfonic acid functional groups are preferred because they can further reduce the electrolysis voltage when the electrolyte membrane is used in a water electrolysis device.
[0107] Hereinafter, an embodiment of the fluorinated polymer having a sulfonic acid type functional group (hereinafter also referred to as “fluorinated polymer (S)”) will be described in detail.
[0108] The fluorinated polymer (S) preferably contains a unit based on a fluorinated olefin and a unit having a sulfonic acid type functional group and a fluorine atom.
[0109] As the fluorinated olefin, for example, a fluorinated olefin having 2 to 3 carbon atoms and having one or more fluorine atoms in the molecule can be cited. Specific examples of the fluorinated olefin include tetrafluoroethylene (hereinafter also referred to as "TFE"), chlorotrifluoroethylene, vinylidene fluoride, vinyl fluoride, and hexafluoropropylene. Among them, TFE is preferred from the perspectives of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0110] The fluorinated olefins may be used alone or in combination of two or more.
[0111] As the unit having a sulfonic acid type functional group and a fluorine atom, a unit represented by formula (1) is preferred.
[0112] Formula (1) -[CF2-CF(-L-(SO3M) n )]-
[0113] L is an n+1-valent perfluorocarbon group which may contain an etheric oxygen atom.
[0114] The etheric oxygen atom may be located at the terminal of the perfluorocarbon group or between carbon atoms.
[0115] The number of carbon atoms in the n+1-valent perfluorocarbon group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0116] L is preferably an n+1-valent perfluoroaliphatic hydrocarbon group optionally containing an etheric oxygen atom, more preferably a divalent perfluoroalkylene group optionally containing an etheric oxygen atom in which n=1 is an embodiment, or a trivalent perfluoroaliphatic hydrocarbon group optionally containing an etheric oxygen atom in which n=2 is an embodiment.
[0117] The divalent perfluoroalkylene group may be linear or branched.
[0118] M is a hydrogen atom, an alkali metal or a quaternary ammonium cation. When M is a plurality of groups, the plurality of groups may be the same or different.
[0119] n is 1 or 2.
[0120] The unit represented by formula (1) is preferably a unit represented by formula (1-1), a unit represented by formula (1-2), a unit represented by formula (1-3), or a unit represented by formula (1-4).
[0121] Formula (1-1) -[CF2-CF(-OR f1 -SO3M)]-
[0122] Formula (1-2) -[CF2-CF(-R f1 -SO3M)]-
[0123] Formula (1-3)
[0124] Formula (1-4)
[0125] R f1 The perfluoroalkylene group is a perfluoroalkylene group which may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0126] R f2 The perfluoroalkylene group is a single bond or may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0127] R f3 The perfluoroalkylene group is a single bond or may contain an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and is preferably 20 or less, more preferably 10 or less.
[0128] r is 0 or 1.
[0129] m is 0 or 1.
[0130] M is each independently a hydrogen atom, an alkali metal or a quaternary ammonium cation.
[0131] As the unit represented by the formula (1-1) and the unit represented by the formula (1-2), the unit represented by the formula (1-5) is more preferable.
[0132] Formula (1-5) -[CF2-CF(-(CF2) x -(OCF2CFY) y -O-(CF2) z -SO3M)] -x is 0 or 1, y is an integer of 0 to 2, z is an integer of 1 to 4, and Y is F or CF3. M is as described above.
[0133] Specific examples of the unit represented by formula (1-1) include the following units: w in the formula is an integer of 1 to 8, and x is an integer of 1 to 5. M in the formula has the same meaning as described above.
[0134] -[CF2-CF(-O-(CF2) w -SO3M)]-
[0135] -[CF2-CF(-O-CF2CF(CF3)-O-(CF2) w -SO3M)]-
[0136] -[CF2-CF(-(O-CF2CF(CF3)) x -SO3M)]-
[0137] Specific examples of the unit represented by formula (1-2) include the following units: w in the formula is an integer of 1 to 8. M in the formula has the same meaning as described above.
[0138] -[CF2-CF(-(CF2) w -SO3M)]-
[0139] -[CF2-CF(-CF2-O-(CF2) w -SO3M)]-
[0140] As the unit represented by the formula (1-3), the unit represented by the formula (1-3-1) is preferred. M in the formula has the same meaning as described above.
[0141] Formula (1-3-1)
[0142] R f4 is a linear perfluoroalkylene group having 1 to 6 carbon atoms, R f5 It is a single bond or a linear perfluoroalkylene group having 1 to 6 carbon atoms which may contain an oxygen atom between carbon atoms. r and M are as defined above.
[0143] Specific examples of the unit represented by formula (1-3-1) include the following.
[0144]
[0145] As the unit represented by formula (1-4), the unit represented by formula (1-4-1) is preferred. f1 , R f2 and M are defined as above.
[0146] Formula (1-4-1)
[0147] Specific examples of the unit represented by formula (1-4-1) include the following.
[0148]
[0149] The unit having a sulfonic acid type functional group and a fluorine atom may be used alone or in combination of two or more.
[0150] The fluorinated polymer (I) may contain units based on other monomers in addition to the units based on the fluorinated olefin and the units having a sulfonic acid type functional group and a fluorine atom.
[0151] Specific examples of other monomers include CF2=CFR f6 (Among them, R f6 It is a perfluoroalkyl group having 2 to 10 carbon atoms. )CF2=CF-OR f7 (Among them, R f7 It is a perfluoroalkyl group having 1 to 10 carbon atoms. )CF2=CFO(CF2) v CF=CF2 (wherein v is an integer from 1 to 3).
[0152] The content of the units derived from other monomers is preferably at most 30 mass % based on the total units in the fluorinated polymer (I) in order to maintain the ion exchange performance.
[0153] The content of the fluorinated polymer (I) is preferably 95 to 100% by mass based on the total mass of the electrolyte membrane.
[0154] <Platinum-containing substances>
[0155] The platinum-containing material may contain platinum atoms. Specific examples of the platinum-containing material include platinum itself, platinum oxides, composite metal oxides containing platinum, and platinum alloys.
[0156] Specific examples of the composite oxide containing platinum include: xPt3O4 (M is at least one metal atom selected from the group consisting of Li, Na, Mg, Ca, Zn, Cd, Co, Ni, Mn, Cu, Ag, Bi and Ce, and x is greater than 0 and less than 1.).
[0157] Specific examples of the platinum alloy include alloys containing at least one metal selected from the group consisting of transition metals and noble metals other than platinum and containing platinum.
[0158] As specific examples of the shape of the platinum-containing material, a granular shape and a flake shape can be cited. When the platinum-containing material is granular, the platinum-containing material can be a core-shell type particle. As an example of a core-shell type particle, a particle having a core of carbon or a metal other than platinum and a shell containing platinum atoms can be cited.
[0159] When the platinum-containing material is in granular form, the average particle size (D50) of the platinum-containing material is preferably greater than 1 nm, more preferably greater than 5 nm, further preferably greater than 10 nm, particularly preferably greater than 100 nm, and preferably less than 10000 nm, more preferably less than 5000 nm, further preferably less than 3000 nm.
[0160] The average particle size of the platinum-containing substance is the cumulative 50% particle size (D50) based on volume obtained by dispersing the dispersion containing the platinum-containing substance using a particle size distribution analyzer. The detailed measurement conditions are as follows.
[0161] After the dispersion containing the platinum-containing substance and the fluorine-containing polymer is dispersed (dispersion treatment based on a bead mill), the particle size distribution is measured by a laser diffraction particle size distribution measuring device (MicrotracBEL Corp., MT3300EXII-SDC) to obtain the volume-based cumulative 50% particle size of the platinum-containing substance. The arithmetic mean of the cumulative 50% particle size at the three points obtained is used as D50.
[0162] Average 1cm 2 The mass of the platinum-containing substance in the electrolyte membrane is preferably 0.010 mg / cm 2 More preferably 0.015 mg / cm 2 More preferably, 0.030 mg / cm 2 Above, particularly preferably 0.040 mg / cm 2 Above, preferably 0.050 mg / cm 2 Below. The mass of platinum-containing material is 0.030 mg / cm 2 When the mass of the platinum-containing material is 0.050 mg / cm 2 When the electrolysis voltage is less than 0.1, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be obtained.
[0163] When the electrolyte membrane has a multilayer structure, the average 1 cm of at least one electrolyte layer (preferably the first electrolyte layer) contained in the electrolyte membrane 2 The mass of the platinum-containing substance in the electrolyte layer is preferably 0.010 mg / cm 2 More preferably 0.015 mg / cm 2 More preferably, 0.030 mg / cm 2 Above, particularly preferably 0.040 mg / cm 2 Above, preferably 0.050 mg / cm 2 Below. The mass of platinum-containing material is 0.030 mg / cm 2 When the mass of the platinum-containing material is 0.050 mg / cm 2 When the electrolysis voltage is less than 0.1, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0164] When the electrolyte membrane is a single-layer structure, the mass ratio of the platinum-containing substance to the fluoropolymer (I) in the electrolyte membrane (mass of the platinum-containing substance / mass of the fluoropolymer (I)) is preferably 0.0005 to 0.0040. When the mass ratio is 0.0005 or more, the occurrence of hydrogen penetration can be further suppressed. When the mass ratio is 0.0040 or less, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0165] In the case where the electrolyte membrane has a multilayer structure, the mass ratio of the platinum-containing substance to the fluoropolymer (I) in at least one electrolyte layer (preferably the first electrolyte layer described above) contained in the electrolyte membrane (mass of the platinum-containing substance / mass of the fluoropolymer (I)) is preferably 0.005 or more, more preferably 0.007 or more, further preferably 0.014 or more, and preferably 0.024 or less. When the mass ratio is 0.005 or more, the occurrence of hydrogen penetration can be further suppressed. When the mass ratio is 0.024 or less, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0166] The platinum-containing substance may be supported on a carrier. Specific examples of the carrier include carbon carriers such as carbon black powder, graphitized carbon, carbon fiber, and carbon nanotube.
[0167] When the platinum-containing material is loaded on a carrier, the loading amount of the platinum-containing material is preferably 10 mass % or more, more preferably 20 mass % or more, further preferably 30 mass % or more, and preferably 50 mass % or less, relative to the total mass of the platinum-containing material and the carrier.
[0168] When the platinum-containing substance is loaded on a carrier, the mass ratio of the carrier loaded with the platinum-containing substance to the fluoropolymer (I) (mass of the fluoropolymer (I) / mass of the carrier) is preferably 10.0 or more, more preferably 30.0 or more, further preferably 60.0 or more, and preferably 500 or less.
[0169] <Cerium Oxide>
[0170] The cerium oxide may be CeO 2 (cerium oxide (IV)) or Ce 2 O 3 (cerium oxide (III)), but CeO 2 is preferred from the viewpoint of stability.
[0171] Cerium oxide can be doped with multivalent metal ions such as zirconium and praseodymium.
[0172] The cerium oxide is preferably in a particulate form.
[0173] When the cerium oxide is in granular form, the average particle size (D50) of the cerium oxide is preferably 1 nm or more, more preferably 5 nm or more, further preferably 10 nm or more, particularly preferably 20 nm or more, and preferably 3000 nm or less, more preferably 2500 nm or less, further preferably 1800 nm or less, particularly preferably 1000 nm or less, and most preferably 400 nm or less.
[0174] When the average particle size of cerium oxide is 1 nm or more, aggregation of cerium oxide is suppressed and a stable dispersion state is easily achieved. When the average particle size of cerium oxide is 3000 nm or less, the chemical durability of the electrolyte membrane can be further improved.
[0175] The method for measuring the average particle size of cerium oxide is as follows.
[0176] After the dispersion containing cerium oxide and fluorine-containing polymer was dispersed (dispersion by bead mill), the particle size distribution was measured by laser diffraction particle size distribution measuring device (MicrotracBEL Corp., MT3300EXII-SDC) to obtain the volume-based cumulative 50% particle size of cerium oxide. The arithmetic mean of the cumulative 50% particle sizes at the three points obtained was used as D50.
[0177] Average 1cm 2 The mass of cerium oxide in the electrolyte membrane is preferably 0.010 mg / cm 2 More preferably 0.029 mg / cm 2 More preferably, 0.043 mg / cm 2 Above, particularly preferably 0.088 mg / cm 2 Above, most preferably 0.132 mg / cm 2 Above, preferably 1.000 mg / cm2 Less than, more preferably 0.500 mg / cm 2 Below, more preferably 0.300 mg / cm 2 the following.
[0178] The mass of cerium oxide is 0.010 mg / cm 2 When the electrolyte membrane is above 100%, the electrolyte membrane becomes whitish, so foreign matter in the electrolyte membrane is easily found. Therefore, when the electrolyte membrane is applied to a water electrolysis device, the electrolyte membrane can be used without using the part where the foreign matter exists, so the generation of pinholes in the electrolyte membrane caused by the foreign matter can be suppressed.
[0179] The mass of cerium oxide is 1.000 mg / cm 2 When the electrolysis voltage is less than 0.1, the electrolysis voltage can be further reduced, and a low-cost membrane electrode assembly and a water electrolysis device can be provided.
[0180] <Method for producing electrolyte membrane>
[0181] As an example of a method for producing an electrolyte membrane, the following method can be mentioned.
[0182] The following method can be cited: First, a mixture of a polymer (hereinafter also referred to as "fluorinated polymer (I')") containing a fluorinated monomer (hereinafter also referred to as a fluorinated monomer (I')) having a group that can be converted into an ion exchange group, a platinum-containing substance, and cerium oxide is used to obtain a membrane P1 containing a fluorinated polymer (I'), a platinum-containing substance, and cerium oxide. Next, the membrane P1, the woven fabric, and the membrane P1 are arranged in this order, and they are stacked using a stacking roll or a vacuum stacking device to obtain a precursor membrane, and then the group that can be converted into an ion exchange group in the precursor membrane is converted into an ion exchange group to obtain an electrolyte membrane containing a fluorinated polymer (I), a platinum-containing substance, cerium oxide, and a woven fabric.
[0183] As another example of the method for producing the electrolyte membrane, the following method can be mentioned.
[0184] The following method can be mentioned: first, the group of the fluorinated polymer (I') that can be converted into an ion exchange group is converted into an ion exchange group to obtain the fluorinated polymer (I). Then, a dispersion containing the fluorinated polymer (I), the platinum-containing substance and the cerium oxide is impregnated into a woven fabric, and then dried to obtain an electrolyte membrane containing the fluorinated polymer (I), the platinum-containing substance, the cerium oxide and the woven fabric.
[0185] By these methods, a single-layer electrolyte membrane (corresponding to the above-mentioned first electrolyte layer) can be obtained.
[0186] An example of a method for producing a multilayer electrolyte membrane is the following method.
[0187] First, a membrane (precursor membrane) comprising a fluorinated polymer (I') and a woven fabric is manufactured, and then the groups in the precursor membrane that can be converted into ion exchange groups are converted into ion exchange groups to obtain an electrolyte membrane A comprising a fluorinated polymer (I) and a woven fabric. In addition, an electrolyte membrane B is obtained by a casting method using a dispersion in which a fluorinated polymer (I), a platinum-containing material and a cerium oxide are dispersed.
[0188] Next, the electrolyte membrane A and the electrolyte membrane B are arranged in this order, and they are stacked using a stacking roll or a vacuum stacking device to obtain an electrolyte membrane comprising a fluorinated polymer (I), a platinum-containing substance, cerium oxide, and a woven fabric. Thus, a multilayer electrolyte membrane is obtained. In the multilayer electrolyte membrane thus obtained, the platinum-containing substance and the cerium oxide are more heavily present on one surface side of the electrolyte membrane.
[0189] Another example of a method for manufacturing a multilayer electrolyte membrane is to laminate a first electrolyte layer comprising a fluorinated polymer (I), a platinum-containing substance, and a cerium oxide and an electrolyte layer (equivalent to the second electrolyte layer) that does not contain a platinum-containing substance or has a lower concentration of platinum-containing substance than the first electrolyte layer, and then perform hot pressing. It should be noted that the woven fabric only needs to be contained in at least one of the first electrolyte layer and the second electrolyte layer. Thus, a multilayer electrolyte membrane is obtained. For the multilayer electrolyte membrane thus obtained, the platinum-containing substance is biased toward one surface side of the electrolyte membrane.
[0190] As the fluorinated polymer (I'), a polymer of a fluorinated monomer (hereinafter also referred to as "fluorinated monomer (S')") having a group that can be converted into a sulfonic acid type functional group (hereinafter also referred to as "fluorinated polymer (S')") is preferred, and a copolymer of a fluorinated olefin and a monomer having a group that can be converted into a sulfonic acid type functional group and a fluorine atom is particularly preferred.
[0191] The fluorinated polymer (S') will be described in detail below.
[0192] As the method for copolymerizing the fluorinated polymer (S'), known methods such as solution polymerization, suspension polymerization and emulsion polymerization can be employed.
[0193] As the fluorinated olefin, there can be mentioned those exemplified above, and TFE is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0194] The fluorinated olefins may be used alone or in combination of two or more.
[0195] Examples of the fluorine-containing monomer (S′) include compounds having one or more fluorine atoms in the molecule, having an ethylenic double bond, and having a group that can be converted into a sulfonic acid type functional group.
[0196] As the fluorinated monomer (S'), a compound represented by the formula (2) is preferred from the viewpoints of the production cost of the monomer, the reactivity with other monomers, and the excellent properties of the obtained fluorinated polymer (S).
[0197] Formula (2) CF2 = CF-L-(A) n
[0198] In formula (2), L and n are as defined above.
[0199] A is a group that can be converted into a sulfonic acid type functional group. The group that can be converted into a sulfonic acid type functional group is preferably a functional group that can be converted into a sulfonic acid type functional group by hydrolysis. As specific examples of the group that can be converted into a sulfonic acid type functional group, -SO2F, -SO2Cl, -SO2Br can be cited. When A is multiple, the multiple A can be the same or different.
[0200] As the compound represented by formula (2), the compound represented by formula (2-1), the compound represented by formula (2-2), the compound represented by formula (2-3), and the compound represented by formula (2-4) are preferred.
[0201] Formula (2-1) CF2=CF-OR f1 -A
[0202] Formula (2-2) CF2=CF-R f1 -A
[0203] Formula (2-3)
[0204] R in the formula f1 , R f2 , r and A are defined as above.
[0205] Formula (2-4)
[0206] R in the formula f1 , R f2 , R f3 , r, m and A are defined as above.
[0207] As the compound represented by the formula (2-1) and the compound represented by the formula (2-1), the compound represented by the formula (2-5) is preferred.
[0208] Formula (2-5) CF2 = CF-(CF2) x -(OCF2CFY) y -O-(CF2) z -SO3F
[0209] The definitions of x, y, z and Y in the formula are the same as those of the compound represented by the above formula (1-5).
[0210] Specific examples of the compound represented by formula (2-1) include the following compounds: wherein w is an integer of 1 to 8, and x is an integer of 1 to 5.
[0211] CF2=CF-O-(CF2) w -SO2F
[0212] CF2=CF-O-CF2CF(CF3)-O-(CF2) w -SO2F
[0213] CF2=CF-[O-CF2CF(CF3)] x -SO2F
[0214] Specific examples of the compound represented by formula (2-2) include the following compounds: wherein w in the formula is an integer of 1 to 8.
[0215] CF2=CF-(CF2) w -SO2F
[0216] CF2=CF-CF2-O-(CF2) w -SO2F
[0217] As the compound represented by the formula (2-3), the compound represented by the formula (2-3-1) is preferred.
[0218] Formula (2-3-1)
[0219] R in the formula f4 , R f5 , r and A are defined as above.
[0220] Specific examples of the compound represented by formula (2-3-1) include the following.
[0221]
[0222] As the compound represented by the formula (2-4), the compound represented by the formula (2-4-1) is preferred.
[0223] Formula (2-4-1) R in the formula f1 , R f2 and A are defined as above.
[0224] Specific examples of the compound represented by formula (2-4-1) include the following.
[0225]
[0226] The fluorinated monomer (S') may be used alone or in combination of two or more.
[0227] In the production of the fluorinated polymer (S'), other monomers may be used in addition to the fluorinated olefin and the fluorinated monomer (S'). Examples of the other monomers include those exemplified above.
[0228] The ion exchange capacity of the fluorinated polymer (I') can be adjusted by changing the content of the group capable of being converted into an ion exchange group in the fluorinated polymer (I').
[0229] Specific examples of the method for converting the groups in the precursor film that can be converted into ion exchange groups into ion exchange groups include a method of subjecting the precursor film to a treatment such as a hydrolysis treatment or an acidification treatment.
[0230] Among them, a method of bringing the precursor film into contact with an alkaline aqueous solution is preferred.
[0231] Specific examples of the method of bringing the precursor film into contact with the alkaline aqueous solution include a method of immersing the precursor film in the alkaline aqueous solution and a method of spraying and applying the alkaline aqueous solution to the surface of the precursor film.
[0232] The temperature of the alkaline aqueous solution is preferably 30° C. or higher, more preferably 40° C. or higher, and preferably 100° C. or lower. The contact time between the precursor film and the alkaline aqueous solution is preferably 3 minutes or higher, more preferably 5 minutes or higher, and preferably 150 minutes or lower, more preferably 50 minutes or lower.
[0233] The alkaline aqueous solution preferably contains an alkali metal hydroxide, a water-soluble organic solvent and water.
[0234] Examples of the alkali metal hydroxide include sodium hydroxide and potassium hydroxide.
[0235] In this specification, a water-soluble organic solvent refers to an organic solvent that is easily soluble in water, and specifically, an organic solvent having a solubility of 0.1 g or more in 1000 ml (20° C.) of water is preferred, and an organic solvent having a solubility of 0.5 g or more is particularly preferred. The water-soluble organic solvent preferably includes at least one selected from the group consisting of aprotic organic solvents, alcohols, and amino alcohols, and particularly preferably includes an aprotic organic solvent.
[0236] The water-soluble organic solvent may be used alone or in combination of two or more.
[0237] Specific examples of the aprotic organic solvent include dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone, and dimethyl sulfoxide is preferred.
[0238] Specific examples of the alcohols include methanol, ethanol, isopropanol, butanol, methoxyethoxyethanol, butoxyethanol, butyl carbitol, hexyloxyethanol, octanol, 1-methoxy-2-propanol, and ethylene glycol.
[0239] Specific examples of amino alcohols include ethanolamine, N-methylethanolamine, N-ethylethanolamine, 1-amino-2-propanol, 1-amino-3-propanol, 2-aminoethoxyethanol, 2-aminothioethoxyethanol, and 2-amino-2-methyl-1-propanol.
[0240] The concentration of the alkali metal hydroxide is preferably 1% by mass or more, more preferably 3% by mass, and is preferably 60% by mass or less, more preferably 55% by mass or less in the alkaline aqueous solution.
[0241] The content of the water-soluble organic solvent is preferably 1% by mass or more, more preferably 3% by mass or more, and is preferably 60% by mass or less, more preferably 55% by mass or less in the alkaline aqueous solution.
[0242] The concentration of water is preferably 39 to 80% by mass in the alkaline aqueous solution.
[0243] After the precursor film is brought into contact with the alkaline aqueous solution, a treatment for removing the alkaline aqueous solution may be performed. As a method for removing the alkaline aqueous solution, for example, a method of washing the precursor film brought into contact with the alkaline aqueous solution with water is exemplified.
[0244] After the precursor film is brought into contact with the alkaline aqueous solution, the resulting film may be brought into contact with an acidic aqueous solution to convert the ion exchange groups into an acidic form.
[0245] Specific examples of the method of bringing the precursor film into contact with the acidic aqueous solution include a method of immersing the precursor film in the acidic aqueous solution and a method of spraying and applying the acidic aqueous solution to the surface of the precursor film.
[0246] The acidic aqueous solution preferably contains an acid component and water.
[0247] Specific examples of the acid component include hydrochloric acid and sulfuric acid.
[0248] [Membrane Electrode Assembly]
[0249] The membrane electrode assembly of the present invention includes the electrolyte membrane, a cathode catalyst layer disposed on one surface of the electrolyte membrane, and an anode catalyst layer disposed on the other surface of the electrolyte membrane.
[0250] Figure 2 FIG. 1 is a cross-sectional view schematically showing an example of a membrane electrode assembly according to the present invention. Figure 2In the example, the membrane electrode assembly 20 includes: an anode 22 having a catalyst layer 26 and a gas diffusion layer 28, a cathode 24 having a catalyst layer 26 and a gas diffusion layer 28, and an electrolyte membrane 10 arranged between the anode 22 and the cathode 24 in contact with the catalyst layer 26.
[0251] exist Figure 2 In the example of FIG. 1 , the electrolyte membrane has a single-layer structure, but the electrolyte membrane may have a multi-layer structure. Specific examples and preferred embodiments of the electrolyte membrane having a multi-layer structure are as described above.
[0252] Figure 3 This is a cross-sectional view schematically showing an example of the membrane electrode assembly of the present invention, and is a view showing a case where the electrolyte membrane has a multilayer structure. Figure 3 The structure of the membrane electrode assembly 120 includes an electrolyte membrane 100 instead of Figure 2 In addition to the electrolyte membrane 10, Figure 2 The structure of the membrane electrode assembly 20 is the same. Figure 3 The electrolyte membrane 100 includes a first electrolyte layer 100A and a second electrolyte layer 100B arranged in this order from the anode 22 side to the cathode 24 side.
[0253] The first electrolyte layer 100A contains a fluorinated polymer (I), a platinum-containing material, and cerium oxide.
[0254] The second electrolyte layer 100B contains a fluorinated polymer (I) and cerium oxide. The second electrolyte layer 100B has a lower concentration of platinum-containing substances than the first electrolyte layer or contains no platinum-containing substances.
[0255] The woven fabric is included in at least one of the first electrolyte layer 100A and the second electrolyte layer 100B.
[0256] exist Figure 3 Although the example of FIG. 1 shows a case where the electrolyte membrane has a two-layer structure, the electrolyte membrane may have a structure of three or more layers.
[0257] exist Figure 3 The example in which only the platinum-containing substance is concentrated on one surface side of the electrolyte membrane is shown, but the electrolyte membrane included in the membrane electrode assembly of the present invention may contain both the platinum-containing substance and the cerium oxide concentrated on one surface side.
[0258] <Anode and cathode>
[0259] The anode and cathode each have a catalyst layer. Figure 2 In this example, the anode 22 and the cathode 24 each have a catalyst layer 26 and a gas diffusion layer 28 .
[0260] Specific examples of the catalyst layer include a layer containing a catalyst and a polymer having an ion exchange group.
[0261] Specific examples of the catalyst include: a supported catalyst containing platinum, a platinum alloy or a platinum catalyst having a core-shell structure supported on a carbon carrier, an iridium oxide catalyst, a composite oxide catalyst containing iridium and other metal elements, an alloy containing iridium oxide, and a catalyst containing iridium oxide having a core-shell structure. As a carbon carrier, carbon black powder can be mentioned.
[0262] Examples of the polymer having an ion exchange group include fluorinated polymers having an ion exchange group, and for example, the above-mentioned fluorinated polymer (I) is used.
[0263] Average 1cm 2 The mass of the catalyst metal in the catalyst layer is preferably 0.05 mg / cm 2 More preferably more than 0.05 mg / cm 2 , more preferably 0.2 mg / cm 2 Above, preferably 4 mg / cm 2 Less than, more preferably 2 mg / cm 2 Below, more preferably 1 mg / cm 2 the following.
[0264] The mass ratio of the catalyst to the polymer having ion exchange groups in the catalyst layer (mass of the catalyst / mass of the polymer having ion exchange groups) is preferably 2-6.
[0265] The catalyst layer preferably contains a thickener from the viewpoint of improving the dispersibility of the catalyst and suppressing aggregation.
[0266] Specific examples of thickeners include urethane thickeners, polyacrylic acid thickeners, polyamide thickeners, cellulose thickeners, clay minerals such as bentonite, etc. In addition, ZEOROLA (registered trademark) H (manufactured by ZEON Corporation of Japan) and the like can also be used as a thickener.
[0267] When the catalyst layer contains a thickener, the content of the thickener is preferably 2 mass % or more, more preferably 3 mass % or more, and preferably 7 mass % or less, more preferably 6 mass % or less, based on the total mass of the catalyst layer-forming coating liquid described below.
[0268] The gas diffusion layer has the function of rapidly diffusing the gas generated by the catalyst layer to the outside of the catalyst layer and the function of being a current collector. Specific examples of the gas diffusion layer include carbon paper, carbon cloth, carbon felt, titanium oxide fiber sintered body, and titanium oxide particle sintered body. The anode side is at a high potential, and if a carbon material is used, it will be oxidized, so it is preferred to use a titanium oxide fiber sintered body or a titanium oxide particle sintered body. The titanium oxide sintered body can be plated with platinum or the like as needed.
[0269] The cathode gas diffusion layer may be subjected to water-repellent treatment using PTFE or the like.
[0270] Figure 2 The membrane electrode assembly includes the gas diffusion layer 28, but the gas diffusion layer is an optional component and the membrane electrode assembly does not necessarily need to include the gas diffusion layer.
[0271] From the viewpoint of further improving the effects of the present invention, the thickness of the anode and cathode is each independently preferably 5 μm or more, and preferably 100 μm or less, more preferably 50 μm or less, further preferably 30 μm or less, and particularly preferably 15 μm or less.
[0272] The film thickness of the anode and the cathode was measured using an image obtained by measuring a cross section cut in the film thickness direction of the membrane electrode assembly using a laser microscope, and the arithmetic mean value was calculated at any 20 locations.
[0273] <Method for Manufacturing Membrane Electrode Assembly>
[0274] The method for producing the membrane electrode assembly is a method in which the cathode catalyst layer is formed on one surface side of an electrolyte membrane, and the anode catalyst layer is formed on the other surface side of the electrolyte membrane.
[0275] As an example of a method for manufacturing a membrane electrode assembly, the following method can be cited: using a stack having an anode catalyst layer and a release substrate (e.g., an ETFE sheet), and a stack having a cathode catalyst layer and a release substrate (e.g., an ETFE sheet), the catalyst layers are bonded to both sides of the electrolyte membrane, and then the release substrate is peeled off.
[0276] The laminate may include a gas diffusion layer between the catalyst layer and the releasable substrate. In this case, the gas diffusion layer may be formed on the surface of the catalyst layer opposite to the electrolyte membrane.
[0277] It should be noted that the method for producing the catalyst layer includes applying a coating liquid for forming the catalyst layer to a predetermined position (e.g., the surface of a release substrate) and drying it as required. The coating liquid for forming the catalyst layer is a liquid in which a polymer having an ion exchange group and a catalyst are dispersed in a dispersion medium.
[0278] <Purpose>
[0279] The membrane electrode assembly of the present invention is suitable for use in a solid polymer water electrolysis device.
[0280] [Water electrolysis device]
[0281] The water electrolysis device of the present invention comprises: the membrane electrode assembly described above; a water supply unit that supplies water to the anode catalyst layer side; and a power supply unit that is electrically connected to the anode catalyst layer side and the cathode catalyst layer side.
[0282] In the water electrolysis device of the present invention, when a DC voltage is applied by the power supply unit while water is supplied to the anode catalyst layer side by the water supply unit, water is decomposed on the anode catalyst layer side to generate oxygen and protons. In addition, on the cathode catalyst layer side, the protons that move to the cathode catalyst layer side via the electrolyte membrane obtain electrons to generate hydrogen.
[0283] The water electrolysis device of the present invention may have the same configuration as a known water electrolysis device (for example, an oxygen recovery member for recovering generated oxygen gas, a hydrogen recovery member for recovering generated hydrogen gas) except for the above-mentioned members.
[0284] Example
[0285] Hereinafter, the present invention will be described in detail with reference to examples. Examples 1 to 5 and Examples 7 to 10 are examples, and Example 6 is a comparative example. However, the present invention is not limited to these examples.
[0286] [Ion exchange capacity of fluorinated polymer]
[0287] The fluoropolymer was placed in a glove box with dry nitrogen for 24 hours, and the dry mass of the fluoropolymer was measured. Thereafter, the fluoropolymer was immersed in a 2 mol / L sodium chloride aqueous solution at 60°C for 1 hour. The fluoropolymer was washed with ultrapure water, taken out, and the liquid immersed in the fluoropolymer was titrated with a 0.1 mol / L sodium hydroxide aqueous solution to obtain the ion exchange capacity (milliequivalent / g dry resin) of the fluoropolymer.
[0288] In addition, in the table|surface mentioned later, IEC (meq / g) means ion exchange capacity (milliequivalent / g dry resin).
[0289] [Thickness of electrolyte membrane]
[0290] The thickness of the electrolyte membrane was measured under the conditions of temperature: 23° C. and relative humidity: 50% RH using an enlarged image (objective magnification: 50 times) of a cross section of the electrolyte membrane photographed using a laser microscope (product name “VK-X1000”, manufactured by KEYENCE CORPORATION).
[0291] [Concentration of hydrogen in oxygen]
[0292] The membrane electrode assembly was sandwiched between platinum-coated titanium fiber sintered bodies (produced by Bekaert) with a thickness of 0.25 mm and a porosity of 60%, and the membrane electrode assembly was installed in an electrode area of 16 cm using a platinum-coated titanium plate with a linear flow path as a spacer. 2 When clamping the membrane electrode assembly, a pressure of 1.5 MPa is applied to the electrode portion to tighten it.
[0293] Next, in order to make the electrolyte membrane and the two electrode ionomers fully hydrated, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 60°C, and normal pressure was supplied to the anode side and the cathode side at a flow rate of 50 mL / min for 8 hours. Thereafter, pure water with a conductivity of 1.0 μS / cm or less and a temperature of 60°C was supplied to the anode side at a flow rate of 50 mL / min, and the back pressure was set to normal pressure at both the anode and the cathode, and was maintained at 16 A (current density 1 A / cm 2 ), and water electrolysis was performed for 4 hours as a warm-up exercise. Then, as a formal measurement, the current density was 0 to 32A (0 to 2A / cm 2 ) range causes the current to increase step by step by 2 A each time.
[0294] Thereafter, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 60°C, and normal pressure was supplied to the battery at 50 mL / min, and the back pressure was set to normal pressure at both the anode and cathode, and the current was maintained at 3.2 A (current density 0.2 A / cm) using a high current constant potential / constant current meter HCP-803 (manufactured by BioLogic). 2 ) for 12 hours. After 12 hours, water was separated from the gas discharged from the anode side, and the hydrogen concentration in the gas was measured by micro GC (Agilent 490, manufactured by Agilent), and the hydrogen concentration in oxygen (H2 concentration in O2) was evaluated according to the following criteria. It can be said that the smaller the value of H2 concentration in O2, the better the low gas permeability of the electrolyte membrane.
[0295] ◎: less than 0.05% by volume
[0296] ○: 0.05 volume % or more and less than 0.10 volume %
[0297] ×: 0.10 volume % or more
[0298] [Fluoride release rate]
[0299] The membrane electrode assembly was sandwiched between platinum-coated titanium fiber sintered bodies (produced by Bekaert) with a thickness of 0.25 mm and a porosity of 60%, and the membrane electrode assembly was installed in an electrode area of 16 cm using a platinum-coated titanium plate with a linear flow path as a spacer. 2 The membrane electrode assembly was clamped and fastened in such a way that a pressure of 1.5 MPa was applied to the electrode portion.
[0300] Next, in order to make the electrolyte membrane and the two electrode ionomers fully hydrated, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 60°C, and normal pressure was supplied to the anode catalyst layer side and the cathode catalyst layer side at a flow rate of 50 mL / min for 8 hours. Thereafter, pure water with a conductivity of 1.0 μS / cm or less and a temperature of 60°C was supplied to the anode catalyst layer side at a flow rate of 50 mL / min, and the back pressure was set to normal pressure in both the anode catalyst layer and the cathode catalyst layer, and was maintained at 16 A (current density 1 A / cm 2 ), and water electrolysis was performed for 4 hours as a warm-up exercise. Thereafter, the water supply to the anode catalyst layer was changed to 150 mL / min, the back pressure was changed to 50 kPa for both the anode and cathode, and the current density was continued for 1000 hours at 1 A / cm 2 The following operation.
[0301] Wastewater discharged from the cathode catalyst layer side was sampled between 500 and 1000 hours after warm-up. The amount of fluoride ions contained in the wastewater was quantified and averaged by ion chromatography, and the average amount of fluoride ions per unit electrode area per unit time was calculated as the fluorine release rate, which was evaluated according to the following criteria. It can be said that the smaller the value of the fluorine release rate, the more the decomposition of the fluorine-containing polymer is suppressed, and the better the chemical durability of the electrolyte membrane.
[0302] ◎: Less than 1.0×10 -6 mg / (h·cm 2 )
[0303] ○:1.0×10 -6 mg / (h·cm 2 ) and less than 3.0×10 -6 mg / (h·cm 2 )
[0304] ×: 3.0×10 -6 mg / (h·cm 2 )above
[0305] [Pinhole]
[0306] The membrane electrode assembly was heat treated at 150° C. for 15 minutes and then placed in a water electrolysis evaluation jig EH50-25 (manufactured by Greenlight Innovation Co., Ltd.).
[0307] Next, first, pure water with a conductivity of 1.0 μS / cm or less, a temperature of 80°C, and normal pressure was supplied to the anode and cathode sides at a flow rate of 50 mL / min for 12 hours in order to fully hydrate the solid polymer electrolyte membrane and the two electrode ionomers. Thereafter, the cathode side was purged with nitrogen.
[0308] After nitrogen purging, pure water with a conductivity of less than 1.0 μS / cm, a temperature of 80°C, and normal pressure was supplied to the anode side at a flow rate of 50 mL / min. The pressure of the generated gas on the cathode side was set to atmospheric pressure. At the same time, a DC power supply PWR1600L manufactured by Kikusui Electronics Co., Ltd. was used to supply a current density of 2 A / cm 2 The machine was operated for 300 hours.
[0309] After the operation, the number of pinholes (openings) in the electrolyte membrane of the membrane electrode assembly was measured using a pinhole inspection device (product name "TRS-70", manufactured by SANKO ELECTRONIC LABORATORY CO., LTD.).
[0310] ◎: No pinholes.
[0311] ○: There are 1 to 2 pinholes.
[0312] ×: The number of pinholes is 3 or more.
[0313] [Example 1]
[0314] First, CF2=CF2 and a monomer (X) represented by the following formula (X) are copolymerized to obtain a fluorinated polymer (I'-1) (ion exchange capacity: 1.25 milliequivalents / g dry resin). It should be noted that the ion exchange capacity in parentheses represents the ion exchange capacity of the fluorinated polymer obtained when the fluorinated polymer (I'-1) is hydrolyzed by the steps described later.
[0315] CF2=CF-O-CF2CF(CF3)-O-CF2CF2-SO2F···(X)
[0316] Next, a mixture containing a fluorinated polymer (I'-1), platinum black ("TEC90300" manufactured by Tanaka Kikinzoku Co., Ltd., a platinum-containing material), and cerium oxide (manufactured by FUJIFILM Wako Pure Chemical Corporation, primary particle size: less than 10 nm, CeO2)) is attached to a substrate formed of a linear low-density polyethylene (LLDPE) film (melting point: 110-120°C) by a melt extrusion method to obtain a substrate Y1 with a film α1 (film thickness: 45 μm) formed on the substrate.
[0317] The warp and weft yarns were made of 18.6 denier yarns made of PFA, and plain weaving was performed so that the density of the PFA yarns was 100 yarns / inch to obtain woven fabric A1. The weight per unit area of woven fabric A1 was 16.3 g / m 2 It should be noted that the warp yarn and the weft yarn are composed of slit yarns.
[0318] The substrate with film Y1 / woven fabric A1 / substrate with film Y1 are stacked in this order. The substrate with film Y1 is arranged so that the film α1 in the substrate with film Y1 is in contact with the woven fabric A1.
[0319] The stacked components were heated to 160°C and subjected to a surface pressure of 30 MPa / m. 2 After heat-compression bonding for 10 minutes using a flat plate press, the substrates on both sides were peeled off at a temperature of 50° C. to obtain a precursor film.
[0320] The precursor film was immersed in a solution of dimethyl sulfoxide / potassium hydroxide / water = 30 / 5.5 / 64.5 (mass ratio) at 95° C. for 30 minutes, and the groups in the precursor film that can be converted into sulfonic acid type functional groups were hydrolyzed and converted into K-type sulfonic acid type functional groups, and then washed with water. Thereafter, the obtained film was immersed in 1M sulfuric acid, and the terminal groups were converted from K-type to H-type, and then dried to obtain the electrolyte membrane 1 (thickness 90 μm) of Example 1.
[0321] A polymer obtained by copolymerizing CF2=CF2 and the above-mentioned monomer (X) and then hydrolyzing and acid-treating to become an acidic polymer (ion exchange capacity: 1.10 milliequivalents / gram of dry resin) is dispersed in a solvent of water / ethanol = 40 / 60 (mass %) at a solid content concentration of 26.0% to obtain a dispersion (hereinafter also referred to as "dispersion Y").
[0322] To the obtained dispersion Y (33.0 g) were added ethanol (18.06 g) and ZEOROLA-H (manufactured by ZEON Corporation, Japan) (10.58 g), and mixed at 2200 rpm for 5 minutes using a rotation-revolution mixer (manufactured by Thinky, Co., Ltd., Awatori Rentaro). To the mixed composition (54.06 g) were added ethanol (46.44 g) and water (75.75 g), and further a 100 m2 iridium having a specific surface area of 74.8% by mass was added. 2 / g of iridium oxide catalyst (produced by Tanaka Kikinzoku Co., Ltd.) (40.0 g) was added. The obtained mixture was treated with a planetary bead mill (rotation speed: 300 rpm) for 90 minutes to obtain an anode catalyst ink having a solid content concentration of 22% by mass.
[0323] Use an applicator to make iridium 1.0 mg / cm 2 The anode catalyst ink was coated on the ETFE sheet in a manner, dried at 80° C. for 10 minutes, and then heat treated at 150° C. for 15 minutes to obtain an anode catalyst layer decal.
[0324] Water (59.4 g) and ethanol (39.6 g) were added to a supported catalyst (“TEC10E50E” manufactured by Tanaka Kikinzoku Kogyo Co., Ltd.) (11 g) in which 46% by mass of platinum was supported on carbon powder, and the mixture was mixed and pulverized using an ultrasonic homogenizer to obtain a catalyst dispersion.
[0325] A mixed solution (29.2 g) obtained by mixing and kneading the dispersion Y (20.1 g), ethanol (11 g) and ZEOROLA-H (manufactured by ZEON Corporation, Japan) (6.3 g) in advance was added to the catalyst dispersion. Furthermore, water (3.66 g) and ethanol (7.63 g) were added to the obtained dispersion, and mixed for 60 minutes using a paint mixer to obtain a solid content concentration of 10.0% by mass to obtain a cathode catalyst ink.
[0326] The cathode catalyst ink was applied to an ETFE sheet using a die coater, dried at 80°C, and then heat treated at 150°C for 15 minutes to obtain a platinum content of 0.4 mg / cm 2 The cathode catalyst layer decal.
[0327] One surface of the electrolyte membrane 1 is opposite to the surface of the anode catalyst layer decal with the catalyst layer, and the other surface of the electrolyte membrane 1 is opposite to the surface of the cathode catalyst layer decal with the catalyst layer, and heating pressing is performed at a pressing temperature of 150°C for 10 minutes and a pressure of 3MPa to join the anode catalyst layer, the electrolyte membrane 1 and the cathode catalyst layer, and the temperature is lowered to 70°C and the pressure is released and taken out, and the ETFE sheets of the anode catalyst layer decal and the cathode catalyst layer decal are peeled off to obtain an electrode with an area of 16cm 2 The obtained membrane electrode assembly was subjected to the above-mentioned evaluations. The results are shown in Table 1.
[0328] In addition, when foreign matter was confirmed during visual inspection of the electrolyte membrane 1, the membrane electrode assembly was produced after removing the foreign matter from the electrolyte membrane 1. The same applies to the following examples.
[0329] [Example 2]
[0330] The content of each component in the kneaded material is appropriately adjusted so that the content of the platinum-containing material in the electrolyte membrane (mg / cm 2 ) and the content (mass %) of cerium oxide became the values shown in Table 1, and a substrate Y2 with a thin film was obtained in which a thin film α2 (film thickness: 45 μm) was formed on the substrate.
[0331] An electrolyte membrane 2 (thickness 90 μm) of Example 2 was obtained in the same manner as in Example 1 except that the substrate Y2 with a thin film was used instead of the substrate Y1 with a thin film.
[0332] The membrane electrode assembly of Example 2 was obtained in the same manner as in Example 1 except that the electrolyte membrane 2 was used instead of the electrolyte membrane 1. The membrane electrode assembly of Example 2 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0333] [Example 3]
[0334] By melt extrusion, a mixture containing a fluorinated polymer (I'-1), platinum black ("TEC90300" manufactured by Tanaka Kikinzoku Co., Ltd., a platinum-containing material), and cerium oxide (manufactured by FUJIFILM Wako Pure Chemical Corporation, primary particle size: less than 10 nm, CeO2) is attached to a substrate formed of a linear low-density polyethylene (LLDPE) film (melting point: 110-120°C), thereby obtaining a substrate Y3 with a thin film having a thin film α3 (film thickness: 30 μm) formed on the substrate.
[0335] An electrolyte membrane 3 (thickness 60 μm) of Example 3 was obtained in the same manner as in Example 1 except that the substrate Y3 with a thin film was used instead of the substrate Y1 with a thin film.
[0336] The membrane electrode assembly of Example 3 was obtained in the same manner as in Example 1 except that the electrolyte membrane 3 was used instead of the electrolyte membrane 1. The membrane electrode assembly of Example 3 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0337] [Example 4]
[0338] The content of each component in the kneaded product is appropriately adjusted so that the content of the platinum-containing substance in the electrolyte membrane (mg / cm 2 ) and the content (mass %) of cerium oxide became the values shown in Table 1, and a substrate Y4 with a thin film was obtained in which a thin film α4 (film thickness: 30 μm) was formed on the substrate.
[0339] An electrolyte membrane 4 (thickness 60 μm) of Example 4 was obtained in the same manner as in Example 3 except that the substrate Y4 with a thin film was used instead of the substrate Y3 with a thin film.
[0340] The membrane electrode assembly of Example 4 was obtained in the same manner as in Example 3 except that the electrolyte membrane 4 was used instead of the electrolyte membrane 3. The membrane electrode assembly of Example 4 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0341] [Example 5]
[0342] The content of each component in the kneaded material is appropriately adjusted so that the content of the platinum-containing material in the electrolyte membrane (mg / cm 2 ) and the content (mass %) of cerium oxide became the values shown in Table 1, and a substrate Y5 with a thin film was obtained in which a thin film α5 (film thickness: 30 μm) was formed on the substrate.
[0343] An electrolyte membrane 5 (thickness 60 μm) of Example 5 was obtained in the same manner as in Example 3 except that the substrate Y5 with a thin film was used instead of the substrate Y3 with a thin film.
[0344] The membrane electrode assembly of Example 5 was obtained in the same manner as in Example 3 except that the electrolyte membrane 5 was used instead of the electrolyte membrane 3. The membrane electrode assembly of Example 5 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0345] [Example 6]
[0346] The fluorinated polymer (I'-1) was attached to a substrate composed of a linear low-density polyethylene (LLDPE) film (melting point: 110-120°C) by melt extrusion to obtain a film-attached substrate Y6 having a film α6 (film thickness: 45 μm) formed on the substrate.
[0347] An electrolyte membrane 6 (thickness 90 μm) of Example 6 was obtained in the same manner as in Example 1 except that the substrate Y6 with a thin film was used instead of the substrate Y1 with a thin film.
[0348] The membrane electrode assembly of Example 6 was obtained in the same manner as in Example 1 except that the electrolyte membrane 6 was used instead of the electrolyte membrane 1. The membrane electrode assembly of Example 6 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0349] [Example 7]
[0350] As Example 7, a membrane electrode assembly was obtained by the following steps and evaluated.
[0351] The contents of the components in the kneaded product are appropriately adjusted so that the content of the platinum-containing substance in the electrolyte membrane is 0.015 mg / cm 2 The content of cerium oxide is 0.008 mg / cm 2 , a substrate Y7 with a thin film is obtained in which a thin film α7 (film thickness: 30 μm) is formed on the substrate.
[0352] An electrolyte membrane 7 (thickness 60 μm) of Example 7 was obtained in the same manner as in Example 3 except that the substrate Y7 with a thin film was used instead of the substrate Y3 with a thin film.
[0353] The membrane electrode assembly of Example 7 was obtained in the same manner as in Example 3 except that the electrolyte membrane 7 was used instead of the electrolyte membrane 3. The membrane electrode assembly of Example 7 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0354] [Example 8]
[0355] As Example 8, a membrane electrode assembly was obtained by the following procedure and evaluated.
[0356] The contents of the components in the kneaded product are appropriately adjusted so that the content of the platinum-containing substance in the electrolyte membrane is 0.030 mg / cm 2 , and the content of cerium oxide is 0.010mg / cm 2 A substrate Y8 with a thin film is obtained in which a thin film α8 (film thickness: 30 μm) is formed on the substrate.
[0357] An electrolyte membrane 8 (thickness 60 μm) of Example 8 was obtained in the same manner as in Example 3 except that the substrate Y8 with a thin film was used instead of the substrate Y3 with a thin film.
[0358] The membrane electrode assembly of Example 8 was obtained in the same manner as in Example 3 except that the electrolyte membrane 8 was used instead of the electrolyte membrane 3. The membrane electrode assembly of Example 9 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0359] [Example 9]
[0360] As Example 9, a membrane electrode assembly was obtained by the following procedure and evaluated.
[0361] The contents of the components in the kneaded product are appropriately adjusted so that the content of the platinum-containing substance in the electrolyte membrane is 0.030 mg / cm 2 , and the content of cerium oxide is 0.008mg / cm 2 A substrate Y9 with a thin film is obtained in which a thin film α9 (film thickness: 30 μm) is formed on the substrate.
[0362] An electrolyte membrane 9 (thickness 60 μm) of Example 9 was obtained in the same manner as in Example 3 except that the substrate Y9 with a thin film was used instead of the substrate Y3 with a thin film.
[0363] The membrane electrode assembly of Example 9 was obtained in the same manner as in Example 3 except that the electrolyte membrane 9 was used instead of the electrolyte membrane 3. The membrane electrode assembly of Example 9 was used and subjected to the above-mentioned evaluation. The results are shown in Table 1.
[0364] [Example 10]
[0365] As Example 10, a membrane electrode assembly was obtained by the following procedure and evaluated.
[0366] The contents of the components in the kneaded product are appropriately adjusted so that the content of the platinum-containing substance contained in the electrolyte membrane formed in the subsequent step is 0.030 mg / cm 2 , and the content of cerium oxide is 0.088mg / cm 2 , a substrate Y10 with a thin film having a thin film α10 (film thickness: 30 μm) formed on the substrate is obtained. That is, in the step of obtaining the substrate Y5 with a thin film, the content of the platinum-containing substance and the content of the cerium oxide are adjusted so as to be twice the mass % of the content of the platinum-containing substance and the content of the cerium oxide in the thin film α5 in the substrate Y5, and the substrate Y10 with a thin film is obtained in the same manner as the substrate Y5 with a thin film.
[0367] In addition, in the step of obtaining the substrate Y6 with a thin film, the same operation as the substrate Y6 with a thin film was performed except that the film thickness was adjusted to 30 μm, thereby obtaining a substrate Y11 with a thin film having a thin film α11 (film thickness: 30 μm) formed on the substrate.
[0368] The electrolyte membrane 10 (thickness 60 μm) of Example 10 was obtained in the same manner as in Example 3 except that the substrate with film Y10 / woven fabric A1 / substrate with film Y11 were stacked in this order.
[0369] The membrane electrode assembly of Example 10 was obtained in the same manner as in Example 3 except that the electrolyte membrane 10 was used instead of the electrolyte membrane 3. The membrane electrode assembly of Example 10 was used and subjected to the above evaluation. It should be noted that the anode catalyst layer was formed in a form arranged on the thin film α10 side of the electrolyte membrane 10. The results are shown in Table 1.
[0370] [Table 1]
[0371]
[0372] As shown in Table 1, it was confirmed that the electrolyte membranes comprising the fluorinated polymer having an ion exchange group, the platinum-containing material, the cerium oxide, and the woven fabric were excellent in low gas permeability and chemical durability (Examples 1 to 5).
[0373] In addition, by comparing Example 2 with the other examples, it was confirmed that the average 2 The mass of platinum in the electrolyte membrane is 0.030 mg / cm 2 More than 1cm on average 2 The mass of cerium oxide in the electrolyte membrane is 0.132 mg / cm 2 In the above case, low gas permeability and chemical durability are more excellent.
[0374] By comparing Example 4 with Example 7, it was confirmed that the average 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.010 mg / cm 2 In the above case, the generation of pinholes can be suppressed.
[0375] In addition, the comparison between Example 8 and Example 9 also confirmed that the average 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.010 mg / cm 2 In the above case, the generation of pinholes can be suppressed.
[0376] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2022-145366 filed on September 13, 2022 are cited herein and incorporated as a disclosure of the specification of the present invention.
[0377] Description of Reference Numerals
[0378] 1, 10, 100 Electrolyte membrane
[0379] 20, 120 membrane electrode assembly
[0380] 22 Anode
[0381] 24 Cathode
[0382] 26 Catalyst layer
[0383] 28 Gas Diffusion Layer
[0384] 100A 1st electrolyte layer
[0385] 100B Second electrolyte layer
[0386] A1, C1 surface
[0387] B1 Depth Position
[0388] T1, T X distance
[0389] X, Y area
Claims
1. A solid polymer electrolyte membrane, characterized in that: Contains: fluorine-containing polymers with ion exchange groups, platinum-containing materials, cerium oxides and woven fabrics.
2. The solid polymer electrolyte membrane according to claim 1, wherein The ion exchange capacity of the fluorine-containing polymer is 0.90 to 2.00 milliequivalents per gram of dry resin.
3. The solid polymer electrolyte membrane according to claim 1, wherein Average 1cm 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.010 mg / cm 2 above.
4. The solid polymer electrolyte membrane according to claim 1, wherein Average 1cm 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.132 mg / cm 2 above.
5. The solid polymer electrolyte membrane according to claim 1, wherein Average 1cm 2 The mass of the platinum-containing substance in the solid polymer electrolyte membrane is 0.030 mg / cm 2 above, Average 1cm 2 The mass of cerium oxide in the solid polymer electrolyte membrane is 0.132 mg / cm 2 above.
6. The solid polymer electrolyte membrane according to claim 1, wherein The platinum-containing substance is concentrated on one surface side of the solid polymer electrolyte membrane.
7. The solid polymer electrolyte membrane according to claim 1, wherein The platinum-containing material is loaded on a carrier.
8. The solid polymer electrolyte membrane according to claim 1, wherein The ion exchange group of the fluorine-containing polymer is a sulfonic acid type functional group.
9. The solid polymer electrolyte membrane according to claim 1, wherein The fluorinated polymer comprises at least one unit selected from the group consisting of a unit represented by formula (1-3) and a unit represented by formula (1-4), In formula (1-3) and formula (1-4), R f1 is a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f2 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, R f3 is a single bond or a perfluoroalkylene group optionally containing an oxygen atom between carbon atoms, r is 0 or 1, m is 0 or 1, and M is each independently a hydrogen atom, an alkali metal or a quaternary ammonium cation.
10. The solid polymer electrolyte membrane according to claim 1, wherein The woven fabric is made of a material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyetheretherketone and polyphenylene sulfide.
11. A membrane electrode assembly, characterized in that: It contains: The solid polymer electrolyte membrane according to any one of claims 1 to 10, a cathode catalyst layer disposed on one side of the solid polymer electrolyte membrane, and An anode catalyst layer is disposed on the other surface of the solid polymer electrolyte membrane.
12. A water electrolysis device, characterized in that: have: The membrane electrode assembly according to claim 11; a power supply unit connected to the cathode catalyst layer side and the anode catalyst layer side of the membrane electrode assembly; and A water supply unit supplies water to the anode catalyst layer side.
13. A method for producing a membrane electrode assembly, the membrane electrode assembly comprising the solid polymer electrolyte membrane according to any one of claims 1 to 10, a cathode catalyst layer and an anode catalyst layer, In the manufacturing method, the cathode catalyst layer is formed on one side of the solid polymer electrolyte membrane, and the anode catalyst layer is formed on the other side of the solid polymer electrolyte membrane.
Citation Information
Patent Citations
Rock breaking tool and crushing method using the tool
JP2022145366A
Membrane electrode assembly, solid polymer electrolyte membrane, waer electrolysis system and electrolytic hydrogenation system
WO2022050363A1